Global climatic changes and the challenge of planetary citizenry - Feldmann, Fabio José; Biderman Furriela, Rachel (Acta Bioethica, 2001)
In this paper we pretend to examine the issue of climatic changes and their crucial consequences for the future of the planet. This subject has been legitimized and made explicit through various world fora, but has undergone poor development in Latin America, although the serious and overriding impacts for the Region. The solution to challenges posed by climatic changes will fundamentally be expressed in the sphere of citizenry and that implies the creation of new forms of dialogue, of dissemination of information, of education, and a process of democratization in decision-making.